Voice & vision : a guide to writing history and other serious nonfiction - Pyne, Stephen J., 1949- (Cambridge, Mass. : Harvard University Press, 2009)
Voice and Vision is for those who wish to understand the ways in which literary considerations can enhance nonfiction writing. At issue is not whether writing is scholarly or popular, narrative or analytical, but whether it is good. --from publisher description
In the beginning, words -- Art and craft -- Rules of engagement -- Nonfiction as writing -- Voice-- -- --and vision -- Designing -- Plotting -- Transitioning -- Dramatizing -- Editing I -- Prose -- Character -- Setting -- Point of view -- Showing and telling -- Editing II -- Figures of speech -- Technical information -- Questions of scale -- Theory and practice -- Writing lives.
Includes bibliographical references (p. [301]-308) and index.
Keywords: Authorship; English language -- Rhetoric; English language -- Style; Historiography